Forecasting Produksi Energi Photovoltaic Menggunakan Algoritma Random Forest Classification - Febtiawan, Ergi Putra; Akbar, Lalu A. Syamsul Irfan; Rachman, A Sjamsjiar (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Solar energy is one of the most affordable energy sources and a clean and friendly renewable energy source in the world. Solar energy, which is abundant throughout the world, can be an energy source that is economical to implement. Due to its advantages, the use of solar energy continues to increase throughout the year. One way to convert solar energy into electrical energy is to use a Photovoltaic (PV) or PV Module device. The PV module used as a study is located in the PLN PLTS 7 MWp in Sengkol village. The PV module used as a study is located in the PLN PLTS 7 MWp in Sengkol village. PV energy production forecasting is carried out to assist in managing planning and knowing PV energy production based on meteorological data in an area where PV equipment has not been installed with a user interface in the form of a website. Machine learning is a technique that allows machines to learn directly from examples, data and experience. In contrast to traditional programming approaches where machines are given commands one by one, machine learning can make its own decisions on a problem after it